2012
DOI: 10.1097/tme.0b013e31826e4bb9
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroid Prescribing From the Emergency Department for Children With Asthma

Abstract: In the article "Frequency of Prescription of Inhaled Corticosteroids to Children With Asthma in U.S. Emergency Departments," the authors conducted a secondary data analysis from the National Hospital Ambulatory Medical Care Survey database to examine inhaled corticosteroid prescribing patterns of providers caring for children with asthma visiting emergency departments. We review and critique this article and use a case study module to illustrate the importance of the research findings and how they relate to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Shedd et al examined the prescribing patterns of ICSs in children with asthma in the ED using the National Hospital Ambulatory Care Survey (NHAMCS) database and concluded that the majority of children and adolescents seen in EDs nationwide for acute respiratory symptoms and asthma are receiving suboptimal care at discharge. 17 A 2007 study that used the National Ambulatory Medical Care Survey (NAMCS) database found that physician incentives and capitated plans are associated with an increase in physicians prescribing controller medications or preventive care in children with asthma. 18 In a previous study in children, patient's age, Medicaid insurance, and Spanish language were associated with inadequate asthma therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Shedd et al examined the prescribing patterns of ICSs in children with asthma in the ED using the National Hospital Ambulatory Care Survey (NHAMCS) database and concluded that the majority of children and adolescents seen in EDs nationwide for acute respiratory symptoms and asthma are receiving suboptimal care at discharge. 17 A 2007 study that used the National Ambulatory Medical Care Survey (NAMCS) database found that physician incentives and capitated plans are associated with an increase in physicians prescribing controller medications or preventive care in children with asthma. 18 In a previous study in children, patient's age, Medicaid insurance, and Spanish language were associated with inadequate asthma therapy.…”
Section: Introductionmentioning
confidence: 99%